AKTIVITAS BELAJAR IPS TERPADU MENGGUNAKAN MODEL TC DAN MAM MEMPERHATIKAN MINAT BELAJAR - Annida Yuswan; Yon Rizal; Pujiati Pujiati (JEE (Jurnal Edukasi Ekobis), 2015)
The purpose of this research was to investigate the social studies learning activity and the interaction between students. Methods which used was quasi experimentation. Based on data analysis, it could be concluded: (1) There was difference between learning activity in social study of students whose learning used the model of TC cooperative learning type than those whose learning used MaM cooperative learning type, (2) Learning activity in social studies who had a high learning interest whose learning using the model of cooperative TC type were higher than those who were learning using the model of MaM cooperative learning type, (3) Learning activity in social studies who had a low learning interest whose learning using the model of cooperative TC type were lower than those who were learning using the model of MaM cooperative learning type, (4) There was interactions between cooperative learning model and learning interest in social studies subjects.Tujuan penelitian ini untuk mengetahui perbedaan aktivitas belajar IPS Terpadu serta interaksi antara model pembelajaran dan minat belajar siswa. Berdasarkan analisis data dapat disimpulkan: (1) Terdapat perbedaan aktivitas belajar IPS Terpadu antara siswa yang pembelajarannya menggunakan model TC dibandingkan dengan model MaM, (2) Aktivitas belajar IPS Terpadu siswa memiliki minat belajar tinggi yang pembelajarannya menggunakan model pembelajaran TC lebih tinggi dibandingkan MaM, (3) Aktivitas belajar IPS Terpadu siswa memiliki minat belajar rendah yang pembelajarannya menggunakan model pembelajaran TC lebih rendah dibandingkan MaM,(4) Terdapat interaksi antara model pembelajaran dan minat belajar siswa pada mata pelajaran IPS Terpadu.Kata kunci :aktivitas belajar, MaM, minat belajar, TC